Panspecies molecular assays detect viral pathogens missed by real-time PCR/reverse-transcriptase PCR among pneumonia patients, Sarawak, Malaysia - Jane K. Fieldhouse; Emily S. Bailey; Teck-Hock Toh; King-Ching Hii; Kerry A. Mallinson; Jakie Ting; John A. Lednicky; Antoinette Berita; Tham Thi Nguyen; Diego Galan; Son T. Than; See-Chang Wong; et al. (Tropical Diseases, Travel Medicine and Vaccines, 2020)
Abstract Background In a year-long pneumonia etiology study conducted June 2017 to May 2018 in Sarawak, Malaysia, 599 patients’ nasopharyngeal swab specimens were studied with real-time polymerase chain reaction (rPCR)/ reverse-transcription (rRT-PCR) assays for respiratory pathogens known to contribute to the high burden of lower respiratory tract infections. The study team sought to compare real-time assay results with panspecies conventional molecular diagnostics to compare sensitivities and learn if novel viruses had been missed. Methods Specimens were studied for evidence of adenovirus (AdV), enterovirus (EV) and coronavirus (CoV) with panspecies gel-based nested PCR/RT-PCR assays. Gene sequences of specimens positive by panspecies assays were sequenced and studied with the NCBI Basic Local Alignment Search Tool software. Results There was considerable discordance between real-time and conventional molecular methods. The real-time AdV assay found a positivity of 10.4%; however, the AdV panspecies assay detected a positivity of 12.4% and the conventional AdV-Hexon assay detected a positivity of 19.6%. The CoV and EV panspecies assays similarly detected more positive specimens than the real-time assays, with a positivity of 7.8% by the CoV panspecies assay versus 4.2% by rRT-PCR, and 8.0% by the EV panspecies assay versus 1.0% by rRT-PCR. We were not able to ascertain virus viability in this setting. While most discordance was likely due to assay sensitivity for previously described human viruses, two novel, possible zoonotic AdV were detected. Conclusions The observed differences in the two modes of amplification suggest that where a problem with sensitivity is suspected, real-time assay results might be supplemented with panspecies conventional PCR/RT-PCR assays.